Sola Scriptura versus Sola fide versus Solum Imperium? Albert S. Geyser en ŉ kontemporêre verstaan van μορφή θεοῦ in die Christus-himne - Slabbert, Martin J. (HTS teologiese studies, 2018)
This article explores Albert Stephanus Geyser’s understanding and application of the Christ-hymn (Phlp 2:6–11), focusing especially on the use of the words μορφή θεοῦ. The tension between a literary-critical approach to the text (Scriptura) versus a dogmatic understanding (Fide) is exposed, as well as the challenge of a political ideology of power (Imperium). Geyser’s understanding and application are measured in terms of the current state of New Testament exegetical research. In the footsteps of Stendahl and contemporary New Testament scholars, legitimacy is given to a socio-political reading of the text. Geyser is appreciated as a public theologian with a deep consideration for the text as the source for theological and socio-political reflection and practice.